Impact of Digitalization on the Indian Economy and Requirement of Financial Literacy - Tegwal, Dr. Vijeyata; Tegwal, Mr. Sunil (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
1st July, 2015 is a day when an initiative was being taken by our honorable Prime Minister Narendra Modi towards “Making India Digital”. The campaign aimed to connect rural areas with high speed internet network and to improve the digital literacy. Indian economy is growing at a fast pace that requires the people to be financial literate to take judicious decisions. After this digitalization, the financial transactions have to be done through internet. So, Digital financial literacy is gaining importance. This paper analyses the importance of financial literacy in today’s world. The finding of the study will identify the obstacles in the execution of various programmes to make India financial literate and strategies to execute these policies effectively and efficiently. Keywords: Jan dhan yojna, digital India, literacy.